Genetic diversity and population structure of humpback whales (Megaptera novaeangliae) from Ecuador based on mitochondrial DNA analyses - Felix, Fernando; Caballero, Susana; Olavarria, Carlos (J. Cetacean Res. Manage., 2023)
Information on the genetic characterisation of humpback whales (Megaptera novaeangliae) wintering off Ecuador (Breeding Stock G) is presented. Mitochondrial DNA was extracted and sequenced from 230 skin samples collected between 2002 and 2008 to establish the genetic diversity of this population. From 182 usable samples, 41 different haplotypes were found, eight of which were new and unique. Haplotype diversity (h ± SD) was estimated to be 0.922 ± 0.012 and the nucleotide diversity (π ± SD) 0.019 ± 0.009. A comparison with other areas within the Southeast Pacific (Colombia and Magellan Strait) and the Antarctic Peninsula suggested panmixia within Breeding Stock G, even though significant differentiation was found with Magellan Strait (p < 0.0001 in both FST and ΦST). An additional analysis with the exact test of population differentiation showed significant differences in haplotype frequencies between breeding areas in Ecuador and southern Colombia (p < 0.01), suggesting some level of stratification at breeding grounds as supported by photo-identification studies. The Ecuadorian dataset included haplotypes reported in all three Southern Hemisphere ocean basins indicating recent gene flow within the Southern Hemisphere. The population showed a male-biased sex ratio in adult animals of 2.16:1. Further research and a larger number of samples from breeding areas in the north (Panama and Costa Rica) are required to appropriately assess the extent of structure in this population.